A theology of the church for the Third Millennium : a Franciscan approach - Osborne, Kenan B. (Studies in Systematic Theology, 2009)
At the beginning of the new millennium, the Christian Churches are in a process of renewal. The Roman Catholic Church, since Vatican II, has been in a major stage of renewal. Contemporary globalization, multi-cultural interrelationships, and inter-religious dialogues have presented serious challenges to these renewal efforts. In this volume, I want to offer to the Catholic Renewal and from there to other denominational renewals, a view of the church from the rich tradition of Franciscan philosophy and theology. To date there are a only a few books which include small essays on this theme. This volume presents an in-depth Franciscan approach to ecclesiology.